2016
DOI: 10.1016/j.numecd.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The association of lean and fat mass with all-cause mortality in older adults: The Cardiovascular Health Study

Abstract: Background and Aims Understanding contributions of lean and fat tissue to cardiovascular and non-cardiovascular mortality may help clarify areas of prevention in older adults. We aimed to define distributions of lean and fat tissue in older adults and their contributions to cause-specific mortality. Methods and Results A total of 1335 participants of the Cardiovascular Health Study (CHS) who underwent dual-energy x-ray absorptiometry (DEXA) scans were included. We used principal components analysis (PCA) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 39 publications
6
73
0
3
Order By: Relevance
“…Low muscle mass contributes to frailty and reflects decreased physiological reserves that may promote unfavourable outcomes under physiological stress such as after surgery or during illnesses because of poorer intrinsic adaptive mechanisms. Previous studies showed lean mass and muscle area to be protective of all‐cause mortality reducing the incidence by 9–20% independently of indicators of obesity (central obesity and fat tissue mass), chronic diseases, and strength . Low ALM/BMI has also been associated with mortality, but it may be possibly explained by factors that are different than those explaining the association between low ALMI and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low muscle mass contributes to frailty and reflects decreased physiological reserves that may promote unfavourable outcomes under physiological stress such as after surgery or during illnesses because of poorer intrinsic adaptive mechanisms. Previous studies showed lean mass and muscle area to be protective of all‐cause mortality reducing the incidence by 9–20% independently of indicators of obesity (central obesity and fat tissue mass), chronic diseases, and strength . Low ALM/BMI has also been associated with mortality, but it may be possibly explained by factors that are different than those explaining the association between low ALMI and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed lean mass and muscle area to be protective of allcause mortality reducing the incidence by 9-20% independently of indicators of obesity (central obesity and fat tissue mass), chronic diseases, and strength. [55][56][57] Low ALM/BMI has also been associated with mortality, 58 but it may be possibly explained by factors that are different than those explaining the association between low ALMI and mortality. For example, a cross-sectional study in Australian (n = 1005, mean age 62) and Korean (n = 376, mean age 58) cohorts showed greater likelihood of having the metabolic syndrome attributed to higher waist circumference, blood pressure, and triglycerides in participants with lower ALM/BMI, while opposite results were observed for sarcopenia as defined by low ALMI (kg/ht 2 ).…”
Section: Other Health Implications Of Low Appendicular Lean Mass: Illmentioning
confidence: 99%
“…Specifically, although the crude body weight was similar between patients with and without physical frailty, the former group had significantly lower lean tissue mass but higher adipose tissue mass (Table 2), indicating concomitant muscle atrophy and accumulation of body fat due to the lack of physical activity. Previous study showed that frailty exacerbates protein catabolism and loss of muscle mass [34], which is related to the cardiovascular and overall mortality in the elderly population [35]. To the best of our knowledge, alterations of adipose tissue mass in frail elderly patients have not been reported previously.…”
Section: Discussionmentioning
confidence: 83%
“…CV risk factors are highly prevalent in patients with NAFLD, and CV mortality contributes significantly to their overall loss of life time . It has been estimated that 5% to 10% of patients with NAFLD die from CVD, and patients with NAFLD exhibit a 2‐fold increased risk of CVD . A meta‐analysis exploring more than 17,000 patient‐years observed CVD to be the leading cause of mortality in patients with NAFLD .…”
Section: Discussionmentioning
confidence: 99%
“…(26) It has been estimated that 5% to 10% of patients with NAFLD die from CVD, and patients with NAFLD exhibit a 2-fold increased risk of CVD. (27,28) A meta-analysis exploring more than 17,000 patient-years observed CVD to be the leading cause of mortality in patients with NAFLD. (6) In a recent exploration of the National Health and Nutrition Examination Survey III, a 42% higher overall mortality rate and doubling of the risk of CV mortality for patients with NAFLD were observed.…”
Section: Discussionmentioning
confidence: 99%